Inferred Response Properties of the Synaptic Inputs Underlying Duration-Tuned Neurons in the Big Brown Bat - Valdizon-Rodriguez, Roberto (My University, 2019)
Duration tuning in the mammalian inferior colliculus (IC) is created by the interaction of excitatory and inhibitory synaptic inputs. We used extracellular recording and paired-tone stimulation to measure the strength and time-course of the contralateral inhibition and offset-evoked excitation underlying duration-tuned neurons (DTNs) in the IC of the awake bat. The onset time of a short, best duration (BD), excitatory probe tone was varied relative to the onset of a longer-duration, non-excitatory (NE) suppressor tone. Spikes evoked by the roving BD tone were suppressed or facilitated when the stationary NE tone was varied in frequency or amplitude. When the NE tone frequency was presented away from the cell’s best excitatory frequency (BEF) or at lower SPLs, the onset of inhibition was relatively constant whereas the offset and duration of inhibition decreased. Excitatory and inhibitory frequency response areas were measured and best inhibitory frequencies matched best excitatory frequencies; however, inhibitory bandwidths were broader than excitatory bandwidths. Excitatory rate-level and inhibitory suppression-level functions were also measured and the dynamic ranges and inflection points were similar, which is hypothesized to play a role in the level tolerance of responses measured from DTNs. We compared the latency of offset-locked facilitation to the onset or offset of inhibition as a function of frequency and amplitude; we found that the facilitation was more related to the onset of inhibition. Moreover, facilitation typically preceded the offset of inhibition – suggesting that it is a separate excitatory input to DTNs and not a rebound from inhibition. We conclude that DTNs receive inputs that generate and preserve temporal selectivity.
Response Properties of Inputs to Duration-Tuned Neurons
Keywords: Auditory Physiology; Temporal Processing; Inferior Colliculus; Electrophysiology; Hearing; Duration Tuning; Neuroscience; Big Brown Bat; Excitatory/Inhibitory Frequency Response Area; Level Tolerance; Rate-Level Function; Suppression-Level Function; Facilitation